Reconfigurable Matched Bandstop Filter - Mohd Khairy, Zahari; Ahmad, Badrul Hisham; Shairi, Noor Azwan; Peng Wen, Wong (2012)
This paper demonstrates a reconfigurable matched bandstop filter. The filter is based on a lossy allpass network. The lossy allpass network demonstrates the concept and design of perfectly matched bandstop response with a perfect matched at all frequencies. The filter is based on the halfwavelength resonator with gap coupling, parallel with an allpass nominally-90°-phase-shift element, which can be optimized to achieve high Q-factor. The reconfigurable matched bandstop filter can be realized by using PIN diodes as a switching element. This filter provides two state of operation under two conditions. The first condition is that the filter will produce allpass response when the PIN diodes are turned ‘ON’. The second condition is that the filter will produce bandstop response when the PIN diodes are turned ‘OFF’. Theoretical analysis together with experimental results is presented in this paper